TINGKAT STRES PADA LANSIA YANG TIDAK TINGGAL SERUMAH DENGAN KELUARGA - enur nurhayati muchsin; Dodik Arso Wibowo; Widyasih Sunaringtyas; Rosyim Viky Ilmika (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Entering old age, a person will experience physical and psychological setbacks, which results in an older person experiencing increased stress quickly, which is caused by external and internal factors. Place of residence and family is one of the causes of increased stress levels in the elderly. Community service aims to provide information and knowledge to the elderly about how to determine the stress level experienced by the elderly who do not live at home with their families. The provision of information and knowledge will be carried out on March 14-19, 2022. The research variable is stress levels in the elderly who do not live at home with their families. The participants were 26 older people. One student assisted them. Using the lecture method, discussion/question and answer. Leaflet media, materials with LCD media and laptops. The results of interviews and filling out questionnaires by the elderly who did not live at home with their families found 26 respondents, indicating that most of the respondents experienced moderate stress, as many as 65% of respondents, almost half of the respondents experienced mild stress, as many as 35% of respondents. The level of stress in the elderly who do not live at home with their family can be stress-free in a way; the elderly can recognize and understand how to prevent stress by participating in activities facilitated by the village or puskesmas at the elderly Posyandu by meeting other older people and participating in elderly gymnastics.